2020
DOI: 10.1086/711162
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Related to the Killing of Michael Brown and Resulting Civil Unrest in Ferguson, Missouri: Roles of Protest Engagement, Media Use, Race, and Resilience

Abstract: A significant body of research has examined the psychological harm of exposure to collective traumas such as disasters (e.g., tornados, hurricanes, mass violence). Less well studied are the mental health effects of exposure to macro-level race-related traumas, such as instances of police violence toward African Americans and subsequent civil unrest that are widely covered by traditional and social media. Method: This study examined posttraumatic stress (PTS) symptoms in a sample of 936 Black and white resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…On the one hand, hope, inspiration, and anger can galvanize Black youth to take action and strive to eradicate the systems of oppression affecting Black communities ( 6 ). On the other hand, increased fear resulting from various modes of engagement and exposure to violence while attending demonstrations can have long-term impacts on their physical and mental health ( 6 , 8 ). Thus, although the engagement of Black youth in movements germane to their racial identity and wellbeing can be empowering, it is important to create opportunities for them to process the stress and trauma related to these activities using culturally relevant methods ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, hope, inspiration, and anger can galvanize Black youth to take action and strive to eradicate the systems of oppression affecting Black communities ( 6 ). On the other hand, increased fear resulting from various modes of engagement and exposure to violence while attending demonstrations can have long-term impacts on their physical and mental health ( 6 , 8 ). Thus, although the engagement of Black youth in movements germane to their racial identity and wellbeing can be empowering, it is important to create opportunities for them to process the stress and trauma related to these activities using culturally relevant methods ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Civic engagement during adolescence can provide youth with an outlet for identity exploration, promote socioemotional competency, and contribute to sustained civic engagement across the lifespan, as well as strengthen feelings of agency, healing, and unity among traumatized communities ( 6 , 7 ). At the same time, engagement may increase adolescents’ vulnerability to harm and negative emotions ( 6 , 8 , 9 ). The majority of quantitative studies on engagement with BLM demonstrations include parent reports about their children or adults’ (18+ years old) accounts of their own experiences.…”
mentioning
confidence: 99%
“…Current research has shown evidence of a positive correlation between secondary exposure to racerelated stress and negative behavioral health outcomes (Martz et al, 2019). Shared racial trauma occurs when both the client and counselor experience the same trauma and increases the possibility of STS or vicarious trauma (First et al, 2020). Comas-Díaz et al (2019) noted that continuing exposure and reexposure to race-based stress (both directly and vicariously) leads to racial trauma.…”
Section: Racism and Race-related Stressmentioning
confidence: 99%
“…Higher levels of racial discrimination are associated with higher levels of trauma symptoms in Black Americans, which, potentially, places Black therapists at higher risk of burnout and STS (Chou et al, 2012;Kirkinis et al 2018). Moreover, Black therapists are navigating the same race-related stresses as their Black clients (First et al, 2020;Lipscomb & Ashley, 2020). Black therapists' perceptions and appraisals of their race-related stresses may overwhelm their ability to cope in their personal and professional settings.…”
Section: Racism and Race-related Stressmentioning
confidence: 99%
“…Janet E. Helms, Guerda Nicolas, and Carlton E. Green further differentiate between the "direct racial or ethnic cultural cataclysmic events" and "vicarious events" (Helms, Nicolas and Green 2010, 55-56), which are rooted in the act of witnessing racist incidents secondhandedly but still inducing trauma. Currently, racial trauma is discussed in relation to mental health's impact of the recent protests against police brutality (First et al 2020). Racial trauma research is a promising context for analyzing BLM-inspired, trauma-centered narratives.…”
Section: Trauma Theory and Cinemamentioning
confidence: 99%